2014
DOI: 10.1111/avsc.12140
|View full text |Cite
|
Sign up to set email alerts
|

Landscape context in colonization of restored dry grasslands by target species

Abstract: Questions: Although the role of landscape context, often interpreted as the available species pool, is generally assumed to be important for the restoration of disturbed sites, not many studies evaluating this role quantitatively in restored dry grasslands have been carried out. There is especially a lack of large-scale, multi-site studies. We asked how many unsown target species established spontaneously in restored dry grasslands and how spontaneous establishment depended on their occurrence in the surroundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 46 publications
(70 reference statements)
4
64
0
Order By: Relevance
“…Similarly, in previous studies greater proximity and connectivity to remnant patches has been shown to increase the richness or abundance of desired species in restorations (Holl & Crone ; Helsen et al ; Mulligan et al ). For example, previous studies have shown decreases in plant richness in restorations with increasing distance from intact communities (Kindscher & Tieszen ; Alsfeld et al ; Winsa et al ), and similar to our study, a positive relationship between richness in restorations and richness in the surrounding landscape (Ashworth et al ; Beltman et al ; Prach et al ). In contrast, sites restored in anthropogenically degraded locations face multiple stressors including increased propagule pressure from invasive species in the immediate surroundings (Ehrenfeld ; Simenstad et al ).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, in previous studies greater proximity and connectivity to remnant patches has been shown to increase the richness or abundance of desired species in restorations (Holl & Crone ; Helsen et al ; Mulligan et al ). For example, previous studies have shown decreases in plant richness in restorations with increasing distance from intact communities (Kindscher & Tieszen ; Alsfeld et al ; Winsa et al ), and similar to our study, a positive relationship between richness in restorations and richness in the surrounding landscape (Ashworth et al ; Beltman et al ; Prach et al ). In contrast, sites restored in anthropogenically degraded locations face multiple stressors including increased propagule pressure from invasive species in the immediate surroundings (Ehrenfeld ; Simenstad et al ).…”
Section: Discussionsupporting
confidence: 92%
“…This increasing biodiversity loss has resulted in the need for restoration of grasslands (Walker et al ). Various methods have been applied in grassland restoration on ex‐arable land (Török et al ; Scotton et al ; Kiehl et al ), but the process of restoration is often a long‐term question and active restoration measures might serve only as a trigger of ecosystem recovery in a long‐lasting succession (Prach et al a ).…”
Section: Introductionmentioning
confidence: 99%
“…Large areas of crop fields have been restored to grasslands by means of different techniques, including sowing a regional species‐rich seed mixture, sowing commercial, commonly available seed mixtures, and spontaneous succession on mown fallows. However, in all the cases, the restoration sites are also exposed to spontaneous colonization (Prach et al a ). In this study, we evaluate the establishment success of target grassland species, which were not sown but established spontaneously in the restored grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true in later stages of successions aged more than 20 years where they usually reached <1% of cover (Řehounková & Prach ; Trnková et al ). These undesirable species generally exhibited lower establishment probability in most of the disturbed sites than desirable species, which is typical if natural and semi‐natural vegetation prevails in the surrounding (Řehounková & Prach ; Prach et al , ). The only exception in the studied sites was black locust ( Robinia pseudacacia ), an alien tree invading various sites in warmer and drier regions of Europe (DAISIE ).…”
Section: Discussionmentioning
confidence: 99%
“…In secondary successions, such as on abandoned arable land, restoration of (semi)natural vegetation also depends on these factors because late successional target species rarely occur in the propagule bank (Cramer & Hobbs ). Spontaneous colonization from outside has been predominantly investigated in the case of restoration of seminatural grasslands on ex‐arable land (e.g., Pärtel et al ; Fagan et al , Lencová & Prach ; Knappová et al ; Prach et al ). Generally, spontaneous succession (i.e.…”
Section: Introductionmentioning
confidence: 99%